Penguatan Pendidikan Karakter Peserta Didik melalui Budaya Literasi Membaca di SD Negeri 1 Wonoanti - Priyadi, Yuri Catur; Setyowati, Eny; Dwi Tyas Widoyoko, Riza (PGSD STKIP PGRI Pacitan, 2025)
This study aims to 1) describe the implementation of reading literacy habituation in low-grade students at SD Negeri 1 Wonoanti; 2) find out the culture of reading literacy forming character in low-grade students at SD Negeri 1 Wonoanti. The type of research is descriptive qualitative. Data collection techniques using observation, interview, and documentation methods. Data analysis techniques use data selection, data presentation, and conclusion drawing. The results showed that 1) reading literacy culture has been implemented at SD Negeri 1 Wonoanti. The implementation of students' reading literacy habituation is implemented through reading literacy habituation activities every 15 minutes before the learning process, Sustained Silent Reading activities, library visit schedules, and through daily activities at school. 2) The character of low-grade students who are formed is a character who likes to read, disciplined character, curiosity character, communicative character and creative character. This shows that students' character education can be formed through literacy culture. Keywords: Literacy culture, Character, Reading literacy